Bahid - Bernardo, Alethea A.
This thesis production is a 12-minute digital video narrative on the inherent discrimination against lesbians, particularly in the workplace. It focuses on a teacher as she goes through the struggles of being a lesbian in a conservative environment. The plot takes in an exclusive for girls' Catholic school where the two main characters work as teachers. Set in a religious environment, both work hard to keep their jobs and their identity intact. The point of the story is that even though they are good in their chosen profession, they were dismissed because of their innate sexuality.